1999
DOI: 10.1038/sj.cdd.4400510
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis by all-trans retinoic acid in the human myeloma cell line RPMI 8226 and negative regulation of some of its typical morphological features by dexamethasone

Abstract: We investigated the effects of all-trans retinoic acid (RA) and dexamethasone (Dex) on the in vitro growth of the human myeloma cell line RPMI 8226. RA inhibited RPMI 8226 cell growth by both antiproliferative effect and induction of apoptosis. Typical morphological and biochemical characteristics of apoptosis including chromatin condensation, apoptotic bodies formation and internucleosomal DNA cleavage were detected after 4 days of treatment with 1 mM RA. In situ TUNEL assay demonstrated that DNA cleavage pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Although some steroid-like structures as medroxyprogesterone acetate have been shown to have a negative effect on stem cell apoptosis [14], most studies have shown that ATRA and dexamethasone had an apoptotic and antiproliferative effect on myeloma cell lines [15, 16]. It was also reported that dexamethasone and ATRA did not increase each other’s effect on apoptosis and cell counts [17]. …”
Section: Discussionmentioning
confidence: 99%
“…Although some steroid-like structures as medroxyprogesterone acetate have been shown to have a negative effect on stem cell apoptosis [14], most studies have shown that ATRA and dexamethasone had an apoptotic and antiproliferative effect on myeloma cell lines [15, 16]. It was also reported that dexamethasone and ATRA did not increase each other’s effect on apoptosis and cell counts [17]. …”
Section: Discussionmentioning
confidence: 99%
“…The most potent inducers of TG‐2 are retinoids, which promote apoptosis in various cells including neurons (Ferrari et al . 1998; Lefebvre et al . 1999).…”
mentioning
confidence: 99%
“…It is induced in cultured cells by various agents including cytokines, such as interleukin-6 (IL-6) (1, 2), cyclic AMP (3-5), activation of the transcription factor, NFB (6 -8), and DNA methylation (9). The most potent inducers of tTG gene expression are retinoids (10 -12), which also promote apoptosis in various cells (13,14), including neurons (15-17).In this context, the history of tTG in Alzheimer's disease (AD) pathogenesis began almost 20 years ago with the report that brain tTG catalyzed cross-linking of neurofilament molecules (18). A decade later, A␤ peptide (19,20) as well as the ␤-amyloid precursor protein (21) were shown to be cross-linked by tTG.…”
mentioning
confidence: 99%
“…It is induced in cultured cells by various agents including cytokines, such as interleukin-6 (IL-6) (1, 2), cyclic AMP (3-5), activation of the transcription factor, NFB (6 -8), and DNA methylation (9). The most potent inducers of tTG gene expression are retinoids (10 -12), which also promote apoptosis in various cells (13,14), including neurons (15-17).…”
mentioning
confidence: 99%